Leaky bucket analysis by means of separate mutually dependent queues. - Hajjar, Bassem. (University of Ottawa (Canada), 1999)
The leaky bucket admission control scheme has been introduced as the congestion control mechanism of choice for Broadband networks. The leaky bucket is flexible and capable of accommodating fluctuations in traffic. In today's high-speed networks, it is preferred over traditional window based flow control as a traffic regulation and congestion avoidance mechanism. This thesis attempts to model the performance of the leaky bucket mechanism by analyzing it in two separate yet mutually dependent queues. This method, due to its simplicity, can easily model variations of the leaky bucket scheme. By separating the analysis of the two queues, the model can be quickly adapted if the assumptions change. In addition, the thesis uses the results to analyze the performance of two variants of the leaky bucket.
Keywords: Engineering, Electronics and Electrical.